Readiness of local authorities in implementing information security management system (ISMS) - Farah Saffarizan Mohd Esa; Nurazean Maarop, supervisor; Faculty of Advanced Informatics School (2014)
Thesis (Sarjana Sains (Keselamatan Maklumat)) - Universiti Teknologi Malaysia, 2014